Synthesis and Characterization of Complexes of Co2+, Ni2+, Cu2+, Zn2+, Cd2+, UO22+ and VO2+ with Biprotic Tridentate Ligand - Gupta, Vikal; Singh, A.V.; Daga, Kailash (Asian Journal of Chemistry, 2010)
The stability constants of chelates of Co2+, Ni2+, Cu2+, Zn2+, Cd2+, UO2+2 and VO2+ with O-(N-pyrrole-2-methyl imino) propanoic acid (H2PP) were determined potentiometrically by Calvin's extension of Bjerrum's method in 30% (v/v) water-ethanol-mixture (μ = 0.1 ,0.05 and 0.1 M NaClO4) at 25, 35, 45ºC respectively. The thermodynamic parameters have also been evaluated. These chelates are characterized by molecular mass measurement, elemental analyses, magnetic moment, 1H NMR and electronic spectral data.